2015
DOI: 10.1111/bjh.13456
|View full text |Cite
|
Sign up to set email alerts
|

Longer‐term follow‐up and outcome by tumour cell proliferation rate (Ki‐67) in patients with relapsed/refractory mantle cell lymphoma treated with lenalidomide on MCL‐001(EMERGE) pivotal trial

Abstract: SummaryPatients with mantle cell lymphoma (MCL) generally respond to first‐line immunochemotherapy, but often show chemoresistance upon subsequent relapses, with poor outcome. Several studies of the immunomodulator, lenalidomide, have demonstrated its activity in MCL including the MCL‐001 study in relapsed/refractory patients who had failed defined prior therapies of anthracyclines or mitoxantrone, cyclophosphamide, rituximab and also bortezomib. We present here the long‐term efficacy follow‐up of the prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…A multicenter open-label phase III study demonstrated superiority of temsirolimus to investigator’s choice therapy with a median PFS of 4.8 months, leading to its approval in Europe 34 . Third, the phase II EMERGE trial confirmed the activity of lenalidomide in patients with progression of disease on bortezomib, with an overall response rate (ORR) of 28% in a heavily pre-treated population and durable efficacy with long-term follow-up, leading to lenalidomide’s approval in the US 31 , 35 . Subsequently, the SPRINT trial conducted by the European MCL Network randomized 254 patients to receive lenalidomide versus investigator’s choice treatment and found a median PFS of 8.7 months in the lenalidomide group compared with 5.2 months in the control population 36 .…”
Section: Relapsed Mantle Cell Lymphomamentioning
confidence: 94%
“…A multicenter open-label phase III study demonstrated superiority of temsirolimus to investigator’s choice therapy with a median PFS of 4.8 months, leading to its approval in Europe 34 . Third, the phase II EMERGE trial confirmed the activity of lenalidomide in patients with progression of disease on bortezomib, with an overall response rate (ORR) of 28% in a heavily pre-treated population and durable efficacy with long-term follow-up, leading to lenalidomide’s approval in the US 31 , 35 . Subsequently, the SPRINT trial conducted by the European MCL Network randomized 254 patients to receive lenalidomide versus investigator’s choice treatment and found a median PFS of 8.7 months in the lenalidomide group compared with 5.2 months in the control population 36 .…”
Section: Relapsed Mantle Cell Lymphomamentioning
confidence: 94%
“…The regimen consisted of an induction phase with 6 cycles of LBR (LEN [by mouth, days [1][2][3][4][5][6][7][8][9][10][11][12][13][14], bendamustine [90 mg/m 2 IV, days 1-2], rituximab [375 mg/m 2 IV, day 1]), cycle duration 28 days, followed by a maintenance phase with singleagent LEN (by mouth, days 1-21), cycle duration 28 days, up to a maximum of 7 cycles (total duration 52 weeks).…”
Section: Treatmentmentioning
confidence: 99%
“…15 Rash is a common side effect of both bendamustine and LEN. [11][12][13][14][15][16]28 R-B was associated with a higher degree of cutaneous toxicity when compared with R-CHOP or R-CVP. 12,18,29,30 Concerning front-line LEN 1 rituximab in MCL, Ruan et al reported grade 3 to 4 rash in 29% of patients, in contrast to ,10% in relapsed/refractory non-Hodgkin lymphoma.…”
Section: Org Frommentioning
confidence: 99%
“…36 Exploratory analyses showed that the proliferation index for Ki-67 (30% cutoff) was significantly associated with a lower CR rate, DOR, and survival in the MCL-001 study. 37 The combination of lenalidomide with other novel agents and with chemotherapy has been evaluated in numerous studies.…”
Section: Application Of Novel Therapy In R/r MCLmentioning
confidence: 99%